2022
DOI: 10.1021/jacs.1c13568
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Proximity Scanning of a Distal Cysteine to Target PI3Kα

Abstract: Covalent protein kinase inhibitors exploit currently noncatalytic cysteines in the adenosine 5′-triphosphate (ATP)-binding site via electrophiles directly appended to a reversible-inhibitor scaffold. Here, we delineate a path to target solvent-exposed cysteines at a distance >10 Å from an ATP-site-directed core module and produce potent covalent phosphoinositide 3-kinase α (PI3Kα) inhibitors. First, reactive warheads are used to reach out to Cys862 on PI3Kα, and second, enones are replaced with druglike warhea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
44
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 83 publications
0
44
0
Order By: Relevance
“…However, the results suggest that the low reactivity toward PKAcα stems from the non-optimal positioning of the FKM warhead in respect to Cys199 of PKAcα and it is not related to the insufficient electrophilicity of FMK warhead which, on the contrary, is highly reactive. Highly reactive warhead could have advantages in the first stage of inhibitor development, but it should be replaced with less reactive electrophile in the course of optimization of the structure of the inhibitor to increase the selectivity of the chemical reaction …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the results suggest that the low reactivity toward PKAcα stems from the non-optimal positioning of the FKM warhead in respect to Cys199 of PKAcα and it is not related to the insufficient electrophilicity of FMK warhead which, on the contrary, is highly reactive. Highly reactive warhead could have advantages in the first stage of inhibitor development, but it should be replaced with less reactive electrophile in the course of optimization of the structure of the inhibitor to increase the selectivity of the chemical reaction …”
Section: Resultsmentioning
confidence: 99%
“…Highly reactive warhead could have advantages in the first stage of inhibitor development, but it should be replaced with less reactive electrophile in the course of optimization of the structure of the inhibitor to increase the selectivity of the chemical reaction. 47 Finally, to confirm that the covalent modification of PKAcα occurs at Cys199 residue, LC-MS/MS analysis of trypsinated compound 4-PKAcα adduct was carried out. The peptide fragment of PKAcα incorporating modified Cys199 (TWTLC 199 GTPEYLAPEIILSK) with mass difference corresponding to the attached compound 4 (MW + 1235 Da) was detected that localized the modification unambiguously to Cys199.…”
Section: Journal Of Medicinalmentioning
confidence: 99%
“…Hypoxia-inducible factor-1alpha (HIF1α) is crucial in varicocele-induced oxidative stress and apoptosis, and we found that PI3K/Akt, mTOR, and HIF-1 signaling pathways play an important role in HIF1α expression by enrichment analysis and review of related literature (Babaei et al, 2021), and by constructing the hub targets PPI network, it was found that HIF1α upstream related targets PIK3CA, AKT1, MTOR may be potential core targets for MLST in treating varicocele-associated male infertility. The protein crystal complexes (7R9V, 3O96, 3JBZ) were selected as docking targets for PIK3CA, AKT1, and MTOR, respectively, and the original ligands (2Q7, IQO, ADP) were used as positive controls, respectively (Wu et al, 2010;Lau et al, 2016;Borsari et al, 2022). The initial conformation and re-docking results of the original ligands were shown in Supplementary Table S2.…”
Section: Affinity Of Mlst Core Components To Potential Targetsmentioning
confidence: 99%
“…First, the noncovalent fragment selectively recognizes and binds to its target by favorable geometric and energetic complementarity. In the meantime, the warhead on the inhibitor is placed in an appropriate position relative to the nucleophilic residue around the pocket, which promotes the occurrence of the covalent-bond formation in the second step [13,14]. Theoretically, the amino acids with nucleophilic groups in the side chains, such as cysteine [9,15], serine [16,17], lysine [18][19][20], and threonine [21], have the potential to react with covalent inhibitors.…”
Section: Introductionmentioning
confidence: 99%